Odpowiedzi

Najlepsza Odpowiedź!
2010-02-01T21:00:26+01:00
A) 2 ( 8 - x ) - 3 ( 9 - x ) = 0
16 - 2x - 27 - 3x=0
-2x-3x=-16 +27
-5x=11 / -5
x= - 11/5
x=- 1 ⅕

b) - ( 3 x + 2 ) + 2 x = 4
-3x - 2 + 2x=4
- 3x + 2x = 4 + 2
x= - 6

c) 3 ( x - 2 ) - 5 x = 10
3x - 6 - 5x= 10
3x - 5x= 10 + 6
- 2x= 16 / 2
- x= 8
x= - 8


d) ( 4 x - 5 ) - 2 ( x + 3 ) = - 9
4x - 5 -2x - 6= - 9
4x - 2x= -9 + 5 + 6
2x= 2 /2
x=1
2010-02-01T21:03:38+01:00
A) 2 ( 8 - x ) - 3 ( 9 - x ) = 0
16-2x-27-3x=0
-5x-11=0
-5x=11/:(-5)
x=-1⅕
b) - ( 3 x + 2 ) + 2 x = 4
-3x-2+2x=4
-x-2=4
-x=4+2
x=-6
c) 3 ( x - 2 ) - 5 x = 10
3x-6-5x=10
-2x-6=10
-2x=10+6
x=-8
d) ( 4 x - 5 ) - 2 ( x + 3 ) = - 9
4x-5-2x-6=-9
2x-11=-9
2x=-9+11
x=1
2010-02-01T21:12:06+01:00
A) 2 ( 8 - x ) - 3 ( 9 - x ) = 0
16 - 2x - 27 +3 x= 0
-11=-x
x=11

b) - ( 3 x + 2 ) + 2 x = 4
-3x -2 +2x = 4
-x =4+2
-x=6
x=-6

c) 3 ( x - 2 ) - 5 x = 10
3x -6 -5x =10
-2x=16
x=-8

d) ( 4 x - 5 ) - 2 ( x + 3 ) = - 9
4x -5 -2x -6 =-9
2x = 2
x=1